Desempenho de leucochrysa sp. (Neuroptera Chrysopidae) em diferentes presas e sua seletividade a produtos fitossanitários - Costa, Simone Silva da (2016)
Green lacewings (Neuroptera: Chysopidae) are predatory insects with potential to be used in biological control programs of agricultural pests. This work aimed to evaluate the biological aspects of Leucochrysa sp. on different prey species and to verify the selectivity of phytosanitary products.The bioassays were conducted in climatized rooms regulated to a temperature of 25 ± 2 °C, 70 ± 10% R.H. and 12h photophase. The insects were individualized in rectangular boxes of 220 mL until the adult emergence. The duration and viability of larval instars and pupal period were evaluated. The formed couples (n = 20) were kept in PVC cages internally coated with sulphite paper. A period of 120 days was established to evaluate the fecundity and fertility of females.The predator had its best performance when fed with eggs, nymphs and pupae of Aleurocanthuswoglumi Ashby, 1915 (Hemiptera: Aleyrodidae); nymhs and adults of Toxopteracitricida (Kirkaldy, 1907) (Hemiptera: Aphididae) and Brevicorynebrassicae (Linnaeus, 1758) (Hemiptera: Aphididae), respectively, whose larval-adult duration ranged from 34.00 to 37.77 days. When submitted to eggs, nymphs and pupae of Aleurodicusmagnificus Costa Lima, 1928 (Hemiptera: Aleyrodidae) as food source, the green lacewing did not complete its cycle.Regarding the polynomial regression analyzes performed to investigate the functional response patterns on the aphids B. brassicae and T. citricida, a type II response was revealed for the second and third instar of the predator, which is represented by an asymptotic curve, in which the predator is increasing the prey consumption until saturation occurs. The functional response pattern was not altered by the influence of different prey stages used in this study.In the IPM the use of agrochemicals should be performed when they present some type of selectivity, thus, Neem based products were evaluated upon eggs and larvae of second and third instars of Leucochrysa sp. The insects were kept in Petri dishes, sprayed and individually transferred to plastic boxes until adult emergence. The larvae were fed with eggs of Anagastakuehniella(Zeller, 1879) (Lepidoptera: Pyralidae). The formed couples (n = 15) from treated eggs, were fed with beer yeast and honey (1: 1).Azamax®; Nim-I-Go® and Emulzinim® were classified as harmless; Ethanolic extract of neem and NeenMax® as slightly harmful, when sprayed on eggs of the predator. Azamax®; Nim-I-Go®, Emulzinim® and Ethanolic extract of neem were classified as harmless when applied to second and third instar larvae. Deltamethrin was considered harmful to eggs and second instar larvae and moderately harmful to third instar larvae.